Abiotic formation of condensed carbonaceous matter in the hydrating oceanic crust - Marie Catherine Sforna; Daniele Brunelli; Céline Pisapia; Valerio Pasini; Daniele Malferrari; Bénédicte Ménez (Nature Communications, 2018)
Thermodynamic calculations suggest that condensed carbonaceous matter should be the dominant product of abiotic organic synthesis during serpentinization of the oceanic crust at Mid-Ocean Ridges. Here the authors report natural occurrences of such carbonaceous matter formed during low temperature alteration.